System-level design and experimental demonstration of a laser power transfer system - Yigit, Hayri; Boyekin, Tahsin; Kalebasi, M. Talha; Sari, A. Yigit; Herdem, Yusuf; Boynuegri, Ali Rifat; Tekgun, Burak; Erdem, Talha; Kumru, Celal F. (ELSEVIER SCI LTD, 2026)
This study presents the design and experimental validation of a laser-based wireless power transfer (LPT) system that integrates electrical, optical, and control subsystems within a unified framework. The proposed setup consists of a silicon carbide (SiC)-based LLC resonant converter driving a high-power laser diode, an optical transmission link of 20 m, and a photovoltaic (PV) receiver equipped with a maximum power point tracking (MPPT) unit. The system was designed to evaluate the feasibility of stable, continuous optical power transfer under realistic alignment and thermal conditions. Experimental results demonstrate that the laser driver achieves an electrical efficiency of 95.96%, while the overall end-to-end LPT efficiency reaches 12.4% at a delivered power level of approximately 99 W. The findings confirm that coordinated design of the driver, optical path, and receiver sub systems can significantly improve operational stability and energy conversion consistency, offering a practical reference for the development of medium-range optical power transfer systems.
Keywords: Wireless power transfer; Laser power transfer; LLC converter; Laser diode; Photovoltaic; Optics; Physics